2020
DOI: 10.1155/2020/8880296
|View full text |Cite
|
Sign up to set email alerts
|

Large Uterine Fibroids in Pregnancy with Successful Caesarean Myomectomy

Abstract: Uterine fibroid is the commonest benign tumour of the female reproductive tract. It occurs in 20–40% of women, whereas the estimated incidence in pregnancy is 0.1–3.9%. Uterine fibroid in pregnancy is usually asymptomatic with complications occurring in 10–30% of cases. The first line of management is conservative with counselling for myomectomy after delivery. However, in the presence of intractable symptoms, both antepartum myomectomy and caesarean myomectomy have been reported to be successfully performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…Eyong E et al also reported good fetal outcomes in patients with uterine fibroids. 18 4% of babies died in the early neonatal period and 4% were intrauterine fetal deaths,comparing well with a local study. 14 Most of the babies with poor outcomes were those who were delivered preterm.…”
Section: Discussionsupporting
confidence: 81%
“…Eyong E et al also reported good fetal outcomes in patients with uterine fibroids. 18 4% of babies died in the early neonatal period and 4% were intrauterine fetal deaths,comparing well with a local study. 14 Most of the babies with poor outcomes were those who were delivered preterm.…”
Section: Discussionsupporting
confidence: 81%
“…It used to be thought of as an operation with potentially disastrous effects on the mother and was used exclusively in cases of pedunculated subserosal fibroids (18). However, there have been cases of intracaesarian myomectomy with no complications (5,10). According to Kwawukume, enucleation of a myoma can be performed with minimal difficulty in pregnancy, since the tissue is softer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the location of the myoma, pain, bleeding, premature membrane rupture, preterm labour, obstruction of delivery, and even miscarriage present as possible ramifications (4). An elective postnatal myomectomy is commonly employed due to the asymptomatic nature of myomas in 70% of cases (5).…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, massive ascites complicating huge uterine fibroid [14] , large uterine fibroid in pregnancy with successful Caesarean section [15] , incarceration of sessile uterine fibroid in incisional hernia [16] , and successful pregnancy after surgery for giant uterine fibroid have all been reported [17] . Huge uterine fibroid mimicking feature of malignancy was reported in 2021 in Port Harcourt [18] , but we have not seen a co-existence of uterine fibroid with a large umbilical hernia in our practice hence this documentation.…”
Section: Introductionmentioning
confidence: 99%